Peculiarities of Using International Legal Standards in the Field of Ensuring the Rights of Persons Sentenced to Deprivation of Freedom in Ukraine - O. S. Pochanska (Bulletin of Kharkiv National University of Internal Affairs)
It is established that international standards in the field of human rights are developed by international organizations and institutions, specified in the process of law enforcement of international judicial agencies, and subsequently applied in certain national systems, directly influencing the development of legislation and national practice of protecting the convicts. It is noted that international standards for ensuring the rights of persons sentenced to imprisonment define the mandatory or recommended for states normative minimum legal status of a convict, including his legal protection and the relevant legalities and responsibilities of state agencies and officials. The content and characteristic features of international legal standards in the field of human rights are determined. The main forms of using international legal norms, principles, rules and recommendations on the legal status of persons sentenced to imprisonment in the national legislation of Ukraine are highlighted; their content is analyzed. It is emphasized that the practical solution to the problem of application of international standards of convicts’ treatment in the penitentiary system of Ukraine, in particular, provides: prevention of prohibited methods of treatment of convicts that degrade their human dignity; ensuring the legality of the activities of the staff of penitentiary institutions and agencies; bringing the conditions of detention of convicts into compliance, providing proper medical care, general education and vocational training of convicts, etc.; creation of an effective system of resocialization and social adaptation of convicts; expansion of public control over the observance of the rights of convicts while serving a criminal sentence in the form of imprisonment.